Studi Kelimpahan Bintang Mengular (Ophiuroidea) di Pesisir Pantai Nyang-Nyang, Bali - Yusuf Arifianto Purnomo; Devi Ulinuha; I Wayan Darya Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2023)
The goal of this study was to determine the habitat characteristics and population density of brittle stars in coastal area of Nyang-Nyang Beach, Bali. To facilitate the process, observations were made between November and January from 3:00 p.m. to 6:00 p.m., when the tide was at its lowest. The methodology of survey and descriptive comparative approach research was used. Purposive sampling was used to determine observation and sampling locations: two stations known to be brittle star habitats were chosen as research sites. The variables observed were two: biota community structure observations of brittle star variables at the genus level, such as abundance, diversity, evenness, and dominance, which were measured using 1 x 1 m plots. Environmental water quality variables such as beach characteristics, pH, salinity, water temperature, Dyssolved Oxygen, and current velocity are observed. Microsoft Excel was used to perform data analysis calculations. According to habitat analysis, the coast of Nyang-Nyang Beach provides an ideal habitat environment for Echinodermata, particularly the Ophiuroidea class, includes brittle stars. Nyang-Nyang beach had the brittle stars density, with 24 ind/m2 recorded. With an H' value of 0.514, but it was classified as having low diversity. The evenness index value on Nyang-Nyang Beach is 0,468, and there is no dominant genus along the coast of Nyang-Nyang beach because the dominance index value on this beach is close to 0.